Wintering, grazing and fattening heifers - Smith, E.F.; Baker, F.H.; Good, D.L.; Coz, R.F.; Mackintosh, D.L. (Kansas Agricultural Experiment Station, 2012)
Thirty good quality Hereford heifer calves, 10 head to a lot, were used in the study They cost 20 cents a pound delivered to Manhattan, Kansas, September 15, 1952. They originated in the Sterling City, Texas, area. From delivery date until November 15, 1952, they were fed prairie hay and 1 pound of soybean oilmeal pellets per head daily. The system of management for each lot follows: Lot 1-wintered on dry bluestem pasture supplemented with 1 ½ to 2 pounds of concentrate feed per head daily, grazed on bluestem pasture May 1 to July 15, full fed in drylot 100 days. Lot 2-wintered on Atlas sorgo silage, prairie hay, 1 pound of soybean pellets, and 2 pounds of corn per head daily; grazed on bluestem pasture May 1 to July 15; full fed in drylot 100 days. Lot 3-wintered on brome pasture until January 1 then moved to drylot. In drylot they were fed sorghum silage, prairie hay, and 1 pound of soybean pellets per head daily. From April 9, 1953, to July 14. 1953, they were grazed on brome pasture' starting July 14 they were full fed grain 100 days in drylot.
Keywords: Beef; Gain; Dressing percentage; Carcass grade; Price